2008
DOI: 10.1002/uog.6135
|View full text |Cite
|
Sign up to set email alerts
|

Isolated or non‐isolated duodenal obstruction: perinatal outcome following prenatal or postnatal diagnosis

Abstract: Objectives To determine whether the pre-or postnatal diagnosis of either isolated or non-isolated duodenal obstruction (DO) is associated with different outcomes. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
2
23
0
1
Order By: Relevance
“…18 Polyhydramnios was in 54.3% of pregnancies in our study, less common than 69% (20/29) and 75% (12/16) in other 2 studies, respectively. 19,20 Accordingly, preterm birth was less frequent (39.3%) in our patients compared with that (72.%; 8/11) reported by Cohen-Overbeek et al 21 We believe that NIPT as an alternative to diagnostic testing would result in a substantially decreased number of invasive sample procedures. Some cases with preterm labor induced by invasive procedures would be saved.…”
Section: What Does This Study Add?mentioning
confidence: 71%
“…18 Polyhydramnios was in 54.3% of pregnancies in our study, less common than 69% (20/29) and 75% (12/16) in other 2 studies, respectively. 19,20 Accordingly, preterm birth was less frequent (39.3%) in our patients compared with that (72.%; 8/11) reported by Cohen-Overbeek et al 21 We believe that NIPT as an alternative to diagnostic testing would result in a substantially decreased number of invasive sample procedures. Some cases with preterm labor induced by invasive procedures would be saved.…”
Section: What Does This Study Add?mentioning
confidence: 71%
“…Although DA has been thought to result from developmental failure of intestinal luminal canalization [18], the exact pathogenesis of DA remains incompletely understood. Previous studies have proposed ischemia or vascular accident as the possible etiology [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…When DA is detected prenatally, many sources suggest the incidence of trisomy 21 is around 30 %, but some authors have reported incidences up to 41 % and 46 % [14–16]. Likewise, the incidence of chromosome anomalies is increased in EA, with an incidence of 6 to 10 % for whole chromosome aneuploidy and an additional 1 to 2 % for copy number variants [17].…”
Section: Discussionmentioning
confidence: 99%